Prioritisation of Dimensions Enhancing Omnichannel Customer Experience using AHP - Pereira, Maria Sancha Ema de Assuncao; Costa, Juao C. (Prabandhan: Indian Journal of Management, 2026)
Purpose : The paper aimed to identify the important dimensions of omnichannel customer experience (OCCE). This was achieved by evaluating their relative importance from the perspective of industry practitioners in the technical consumer goods sector. Methodology : The study incorporated five dimensions of OCCE, which were proposed by Shi et al. (2020). As part of the study, a total of 29 industry experts were chosen from the technical consumer goods sector across India and consulted, and their inputs were obtained on the relative importance of each of these five OCCE dimensions. Their responses were then further analyzed using the analytic hierarchy process (AHP), and the dimensions were then prioritized by assigning weights to the OCCE dimensions and sub-dimensions. Findings : Connectivity emerged as the most important dimension of OCCE, which was followed by consistency and flexibility. However, personalization and integration emerged as the least important of all the dimensions of OCCE. Originality : This research applied AHP to rank which are the most important dimensions of OCCE, which represented a novel and interesting approach in this field. Since the past literature had not examined these dimensions in detail, this study provided a meaningful contribution toward understanding omnichannel strategies. Practical Implications : Brands and retailers belonging to the technical consumer goods sector can benefit from this study by using it as a guide to develop their omnichannel business segment. By identifying the most important omnichannel dimensions, the findings of this study inform how omnichannel platforms should be used and implemented to improve customer experience.